Efforts To Improve Science Process Skills Through The Implementation of Project-Based Learning Approaches at MIM Tinggarjaya - Rachmah, Uun Fitriana; Khasanah, Uswatun; Hasanah, Uswatun; Ariana, Uti (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the science process skills of fourth grade students in Natural Sciences (IPA) through the application of a project-based learning approach. Science process skills include observation, classification, data interpretation, designing experiments, and communicating research results. However, in practice, many students have difficulty in developing these skills due to learning methods that are still centered on the teacher and do not actively involve students in exploration and problem solving. This study uses a classroom action research (CAR) method consisting of two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. The subjects of the study were 24 fourth grade students of MIM Tinggarjaya. Data collection techniques were carried out through observation, interviews, tests, and documentation. The data obtained were analyzed descriptively qualitatively and quantitatively to see the development of students' science process skills from each learning cycle. The results showed that the application of project-based learning was able to significantly improve students' science process skills. In the first cycle, students' process skills were still in the sufficient category with an average score of 65. However, after improvements and strengthening of learning strategies in the second cycle, the average score increased to 82, with more than 80% of students reaching the good to very good category. This improvement can be seen from the increasing ability of students to make observations, make hypotheses, conduct simple experiments, and present research results in the form of reports or presentations. The conclusion of this study is that the project-based learning approach can be an effective solution in improving students' science process skills. With project-based learning, students are more active, creative, and able to develop critical thinking skills and problem solving in a scientific context. Therefore, it is recommended for educators to integrate this approach into science learning in order to improve the quality of learning and student learning outcomes.